The association of pre-operative body pain diagram scores with pain outcomes following total knee arthroplasty - Dave, Amish J. (Osteoarthritis Cartilage, 2016)
OBJECTIVE: Approximately 20% of total knee arthroplasty (TKA) recipients have suboptimal pain relief. We evaluated the association between pre-surgical widespread body pain and incomplete pain relief following TKA. METHOD: This prospective analysis included 241 patients with knee OA undergoing unilateral TKA who completed questionnaires preoperatively and up to 12 months post-operatively. Questionnaires included the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain scale and a body pain diagram. We derived the number of non-index painful body regions from the diagram. We used Poisson regression to determine the association between painful body regions identified preoperatively and both WOMAC pain at follow-up and improvement in pain as defined by the minimal clinically important difference (MCID). RESULTS: Mean subject age was 66 years (SD 9), and 61% were females. Adjusting for age, sex, co-morbid conditions, baseline pain, pain catastrophizing, and mental health, we found that more widespread body pain was associated with a higher likelihood of reporting 12-month WOMAC pain score >15 (relative risk [RR] per painful body region 1.39, 95% CI 1.18–1.63) and a greater likelihood of failing to achieve the MCID (RR 1.47, 95% CI 1.16–1.86). ). Pain catastrophizing was an independent predictor of persistent pain and failure to improve by the MCID (RR 3.57, 95% CI 1.73–7.31). CONCLUSIONS: Pre-operative widespread pain was associated with greater pain at 12-months and failure to reach the MCID. Widespread pain as captured by the pain diagram, along with the pain catastrophizing score, may help identify persons with suboptimal TKA outcome.